The Value of Progression-Free Survival in Metastatic Breast Cancer: Results From a Survey of Patients and Providers. Issue 1 (June 2019) - MacEwan, Joanna P.; Doctor, Jason; Mulligan, Karen; May, Suepattra G.; Batt, Katharine; Zacker, Christopher; Lakdawalla, Darius; Goldman, Dana
Background. Value assessments and treatment decision making typically focus on clinical endpoints, especially overall survival (OS). However, OS data are not always available, and surrogate markers may also have some value to patients. This study sought to estimate preferences for progression-free survival (PFS) relative to OS in metastatic breast cancer (mBC) among a diverse set of stakeholders—patients, oncologists, and oncology nurses—and estimate the value patients and providers place on other attributes of treatment.Methods. Utilizing a combined conjoint analysis and discrete choice experiment approach, we conducted an online prospective survey of mBC patients and oncology care providers who treat mBC patients across the United States.Results. A total of 299 mBC patients, 100 oncologists, and 99 oncology nurses completed the survey. Virtually all patients preferred health state sequences with contiguous periods of PFS, compared with approximately 85% and 75% of nurses and oncologists, respectively. On average, longer OS was significantly ( P < 0.01) preferred by the majority (75%) patients, but only 15% of nurses preferred longer OS, and OS did not significantly affect oncologists' preferred health state. However, in the context of a treatment decision, whether a treatment offered continuous periods of stable disease holding OS constant significantly affected nurses' treatment choices. Patients and providers alike valued reductions in adverse event risk and evidence from high-quality randomized controlled clinical trials.Conclusions. The strong preference for observed PFS suggests more research is warranted to better understand the reasons for PFS having positive value to patients. The results also suggest a range of endpoints in clinical trials may have importance to patients.